ANALYSIS OF METAL CONTENT OF Pb, Cu, and Zn IN SEDUT SNAIL (Cerithidea cingulata) FROM COASTAL WATERS OF MAROK TUA VILLAGE AND KUALA RAYA VILLAGE, SINGKEP ISLAND, LINGGA REGENCY OF RIAU ARCHIPELAGO PROVINCE - Tengku Rahma Lopi; Irvina Nurrachmi; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe objective of the research is to find out metal content of Pb, Cu, and Zn in Sedut Snail (Cerithidea cingulata) from coastal waters of Marok Tua Village and Kuala Raya Village and determined safe limit of consumption Sedut Snail (Cerithidea cingulata) from coastal waters of Marok Tua Village and Kuala Raya Village. This research has been conducted in coastal waters of Marok Tua Village and Kuala Raya Village, Singkep Island, Lingga Regency of Riau Archipelago Province. The methods used is purposive sampling to determine the definite limits of Marok Tua Village and Kuala Raya Village. Sampling has been conducted on January, 2018 and sample destruction, analysis of metal content conducted in Marine Chemistry Laboratory, Department of Marine Science, Faculty of Fishery and Marine, University of Riau. The result shows that the metal content of Pb was from3,3493 - 4,8570 μg/gat Marok Tua Village and 6,1227 - 6,9880 μg/gat Kuala Raya Village. The metal content of Cu was from51,1067 – 68,1987 μg/g at Marok Tua Village and 92,9733 – 122,3533 μg/gat Kuala Raya Village. The metal content of Zn was from 53,7133 – 61,8427 μg/g at Marok Tua Village and34,4013 – 41,8013 μg/g at Kuala Raya Village. Safe limit of consumption of metal content of Pb, Cu and Zn in coastal waters of Marok Tua Village was 1,6381; 17,091; 33,346 kg/minggu and in coastal waters of Kuala Raya Village was 1,0726; 9,3030; 52,6707 kg/minggu. Keywords: Metal content of Pb, Cu, and Zn, Sedut Snail (Cerithidea cingulata),Marok Tua Village, Kuala Raya Village